Community Based Tourism Dalam Pengelolaan Obyek Wisata Tukad Bindu Kesiman, Kota Denpasar - Adi Saputra, I Putu Agus; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2021)
Community Based Tourism (CBT) is a means of a progressive tourism activity itself, a tourism development based on its community or which is known as Community Based Tourism (CBT). In Kesiman, Denpasar City, especially in Banjar Ujung, there is a tourist destination which uses community-based tourism concept where all of the activities of this place are managed and ran by the community itself. Tukad Bindu puts forward the concept of environmentally friendly by highlighting its main feature which is a river that is plastic-free and has done naturalization, which makes the river its main attraction and also gives a plus point for the place. Not only its river, the location of this place is in Denpasar City which makes this a stand out thew for the city. In its management, there are some factors which affect the optimalization because the management is still on progress. Keywords: Tourism, management, optimaliza, community based tourism